Outcomes of kidney‐transplanted patients with history of intestinal reconstruction of the urinary tract. Issue 1 (3rd September 2021) - Gueguen, Juliette; Timsit, Marc‐Olivier; Scemla, Anne; Boutin, Jean‐Michel; Bruyere, Franck; Longuet, Hélène; Sberro‐Soussan, Rebecca; Legendre, Christophe; Anglicheau, Dany; Büchler, Matthias
Abstract: Background: Due to increased risk of pyelonephritis, patients with intestinal reconstruction of the lower urinary tract (IRLUT) have long been advised against kidney transplantation. The aim of this study was to compare the outcomes of transplantation between patients with IRLUT and patients with normal LUT (NLUT) using propensity score matching method. Methods: The study included 23 kidney recipients with IRLUT matched to 46 kidney recipients with NLUT using known allograft survival and pyelonephritis risk factors as covariates. One‐, 5‐, and 10‐year graft survival, pyelonephritis, and surgical complications occurrence and graft function were compared. Results: One‐, 5‐, and 10‐year graft survival were 96%, 91%, and 63% in the IRLUT group and 96%, 88%, and 70% in the NLUT group, respectively ( p = 0.72). Patients with IRLUT had increased cumulative risk of pyelonephritis at 10 years (70% vs. 19%; log‐rank < 0.01) without impacting graft function or rejection occurrence. There was no difference in overall surgical complication, but patients with IRLUT had more urological complications than patients with NLUT (62% vs. 28%; p < 0.01). Conclusions: Our case‐control study consolidates the results regarding the safety of transplantation in patients with IRLUT using a strong validated matching method and provides new insights regarding graft function, pyelonephritis, and surgical complications in this population.